Pendidikan Karakter dalam Islam Perspektif Al-Qur’an dan Hadits - Yan Surudin; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Character education in Islam is a fundamental concept that refers to the formation of noble qualities and good morals in individuals. The Al-Qur'an and Hadith are two sources of Islamic teachings that provide a strong foundation in character education. The instillation of good character values was exemplified by the Prophet SAW. as a good role model for the Islamic ummah. Character education should start from an early age because at this stage children not only learn academic knowledge, but also develop values, attitudes and social skills that will shape their personalities in the future. When they are children, they will be able to absorb various information quickly, therefore character education is very necessary in forming a child's personality by providing an understanding of Islam based on the Al-Qur'an and Hadith, as well as by emulating the personal example of the Prophet Muhammad SAW. The aim of this research is to find out the concept of character education in Islamic education from the perspective of the Koran and Hadith. The research method used is a qualitative method with a library research approach, namely by obtaining information from books, magazines, journals, documents, historical records or in other words the facilities contained in the library. The results of this research explain character education, how character education is based on Islam and the basis for character education based on the Al-Qur'an and Hadith..